Samrat Upadhyay’s “During the Festival”: A Psychoanalytic-Feminist Exploration of Desire (Kaumodaki: Journal of Multidisciplinary Studies, 2024)
This research delves into Samrat Upadhyay’s short story “During the Festival,” collected in  Arresting God in Kathmandu, examines the innate impulses shared by humans and animals within the modern Nepali society. Through a psychoanalytic-feminist theoretical framework, the study critically uncovers the subconscious projections of characters like Ganesh, revealing the complex dynamics of jealousy, sexuality, and familial relationships. Ganesh’s jealousy towards his wife’s emotional relationship with a young man in the neighbourhood reflects deeper insecurities about sexuality and societal norms and values in Nepal, while the neighbour’s displacement of his wife with his mother exposes the unresolved and conflicting issues stemming from the childhood experiences. Drawing on psychoanalytic principles, the analysis explores the themes of infantile fears and psychical metamorphosis, shedding light on the intricate interplay between individual psyche and societal constructs. By dissecting the text’s intrinsic characters and unconscious desires, this research contributes to a deeper understanding of human nature and societal complexities in Nepali literature.